Liver ductal organoids reconstruct intrahepatic biliary trees in decellularized liver grafts. (August 2022) - Tomofuji, Katsuhiro; Fukumitsu, Ken; Kondo, Jumpei; Horie, Hiroshi; Makino, Kenta; Wakama, Satoshi; Ito, Takashi; Oshima, Yu; Ogiso, Satoshi; Ishii, Takamichi; Inoue, Masahiro; Hatano, Etsuro
Abstract: Three-dimensional scaffolds decellularized from native organs are a promising technique to establish engineered liver grafts and overcome the current shortage of donor organs. However, limited sources of bile duct cells and inappropriate cell distribution in bioengineered liver grafts have hindered their practical application. Organoid technology is anticipated to be an excellent tool for the advancement of regenerative medicine. In the present study, we reconstructed intrahepatic bile ducts in a rat decellularized liver graft by recellularization with liver ductal organoids. Using an ex vivo perfusion culture system, we demonstrated the biliary characteristics of repopulated mouse liver organoids, which maintained bile duct markers and reconstructed biliary tree-like networks with luminal structures. We also established a method for the co-recellularization with engineered bile ducts and primary hepatocytes, revealing the appropriate cell distribution to mimic the native liver. We then utilized this model in human organoids to demonstrate the reconstructed bile ducts. Our results show that liver ductal organoids are a potential cell source for bile ducts from bioengineered liver grafts using three-dimensional scaffolds.